IMPLEMENTASI PROGRAM PENGEMBANGAN LIMA TAHUN ANTARA INDONESIA-CHINA TERHADAP SEKTOR PERTANIAN INDONESIA (2013-2017) - Novi Amelia; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is about bilateral relations between Indonesia and China within the Five Years Development Program.Indonesia-China has enjoyed economic and trade cooperation for a long time. Like the other cooperation, Indonesia - China Five-Year Development Program aims to expand and deepen comprehensive cooperation between Indonesia and China. Both sides have identified areas of cooperation for the next five years: agriculture, fisheries, energy, mining, transportation, infrastructure, public works, communications, manufacturing, services and industrial parks.The purpose of this research is to explain how the implementation of the Indonesia China Five-Year Development Program towards Indonesia agriculture sector in 2013-2017. This study used qualitative research methods. In this study, the author uses a liberal perspective with the theory of international cooperation with an analysis of levels in the nation-state. And the technique of collecting data through library researchThe results shows that there is the implementation of Indonesia-China Five Year Development Program towards Indonesia Agriculture Sector in 2013-2017 runs well or in the sense of being implemented. This can be seen from the results increase in rice production national, the increase in the value of Indonesian CPO exports to China year (2013-2017), the increased investment of investors from China who invested in Indonesia.Keywords:Implementation, Indonesia-China, hybrid-rice, CPO